“Estrategias colaborativas en entornos virtuales” - Muñoz Cisneros, Diego Alexander (2022)
Currently, education requires the incorporation of various collaborative strategies in virtual environments during the didactic process, since they have been acquiring increasing importance and evolving over the last few years, therefore, it is important to create virtual scenarios. innovations that motivate students to learn. It should be added that virtual platforms are fundamental because it is the space that creates educational content for the exchange of knowledge between teachers and students, that is, collaboration is promoted through platforms that favor interactions to carry out the teaching-learning process and development of interpersonal skills. So, traditional resources do not respond to the needs of the students of this century, since they focus only on traditional, rote and monotonous learning. Given this is added the lack of teacher training in the use and management of digital platforms. Therefore, the objective of the research is to promote the use of collaborative strategies through virtual environments for cognitive development in sixth-year students of Basic General Education of the "José Mejía Lequerica Educational Unit" of the Salcedo canton, Cotopaxi Province, year school year 2021-2022. The methodology used for the development of this project is part of qualitative research because it allows us to understand the reality of the educational context, in addition, the stages that are: preparatory, field work, analytical and informative, were used to the search for information in relation to the variables of the object of study, field research was also used for data collection. The method used in this work is the inductive method. The technique used is the interview with its interview guide instrument, which allowed obtaining information from the research subjects of the educational unit to implement new collaborative strategies within the virtual environment. The results are satisfactory because the use of innovative strategies will be analyzed where the teacher has the possibility of handling technology correctly together with their students, creating collaborative spaces where students develop their critical thinking in each virtual environment. In this way, it will improve synchronous meetings where teachers and students obtain benefits when using digital platforms. This will serve to develop collaborative learning in students, in such a way that it is possible to capture attention, interest and motivation through the use of resources. technology, which will generate improvements in student learning.